PERAN PERPUSTAKAAN STAIN KEDIRI DALAM LAYANAN PEMUSTAKA (Kajian Kualitas Layanan Perpustakaan Berdasarkan Persepsi Pemustaka) - Komarudin; M. Basit Aulawi; Djuwandana Pamungkas (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2016)
The role and function of library in service to its users is to meet the need for information. This study aimed to evaluate quality of library services based on users perception, to measure level of satisfaction of users to the State College of Islamic Studies (STAIN) Kediri library services. This quantitative research uses LibQUAL+ survey method by measuring three dimensions : affect of service, information control, and library as place. Respondents of this study are 257 users of STAIN Kediri Library. Sample are selected by proportionate stratified random sampling technique.The results showed that the quality of STAIN Kediri library services, based on the users perception, meet minimum users expectations. Based on the level of satisfaction, the library services meet users expectations and they are quite satisfied with the services of STAIN Kediri Library. The gap between perceptions and expectations indicate that the users are quite satisfied with the services and the quality of STAIN Kediri Library services are within the zone of tolerance an area that lies between the minimum expectation and ideal expectation of library services quality.